(untitled) (Journal of Hama University, 2020)
Objective: The objective of this study was to assess treatment effects on skeletal and dental changes in skeletal class II patients after treatment with either Herbst appliance or Korn mandibular advancer as fixed functional appliances by means of lateral cephalometric radiographs. Materials and Methods of study: The sample of study consisted of (30) patients divided into two groups (G1): group one included (15) patients who were treated by Korn mandibular advancer appliance, and (G2): group two was treated by Herbst appliance. In both groups fixed functional appliances were applied concurrently with fixed orthodontic appliance. Lateral cephalograms were taken and analyzed before treatment and after treatment. Statistical analyses were used to analyze data by ( Kolmogorov smirnov, K-S) and student’s t tests. Statistical significance was set at P<0.05. Results: For both FFAs, improvement in skeletal discrepancy and interincisal angle was achieved after treatment. Significant reduction of overjet and overbite was noticed in both groups.. Decrease in angle between upper incisor and palatal plane was significantly greater in Herbst appliance more than Korn appliance. Conclusions: Decrease in SNA angle was observed in both FFAs after treatment which was in Herbst patients more than Korn group which indicated retardation of maxillary growth. Increase in SNB angle in both FFAs after treatment was noticed which indicated activation of mandibular growth, Also we recorded significant decrease in ANB angle for both FFAs after treatment which lead to improvement of skeletal discrepancy. Significant decrease in overjet and overbite was achieved in both FFAs used in study.